Against the Mind of a Mindless Age, the Power of Computers and the Destruction of Reason: Responsibility for a Humane Development of Technology and Society - Klaus Fuchs-Kittowski (tripleC: Communication, Capitalism & Critique)
World peace demands a great moral effort from humans. In this contribution, the author points out the moral responsibility of computer scientists. He argues that we live in a mindless age where reason is being destroyed, which results in the devastation of Humanism. It is argued that war is not a natural and necessary feature of humanity and society but has a societal character. Anti-Humanism, would, however, propagate hatred. It is argued that the assumption that humans can or should be replaced by computers is part of contemporary anti-Humanism. The author stresses that humans are different from animals and computers. Humans can act like animals and computers but they do not have to as they have free will. Autological thought is identified as a line of thinking that supports Humanism. There is a tendency in AI research to take and advance anti-Humanist positions. The outlined Humanism is based on approaches such as the ones by Karl Marx, Emil Fuchs, Salvador E. Luria, theories of self-organisation, Georg Lukács, Ernst Bloch, and Christoph Seidler. The paper argues that scientific and technological progress alone is not enough but needs to be accompanied by and integrated with social responsibility and societal progress. It is suggested that a genuine communication society is created where we are human beings among human beings.